2015
DOI: 10.1002/adma.201501167
|View full text |Cite
|
Sign up to set email alerts
|

Pt/Ta2O5/HfO2−x/Ti Resistive Switching Memory Competing with Multilevel NAND Flash

Abstract: Pt/Ta2 O5 /HfO2- x /Ti resistive switching memory with a new circuit design is presented as a feasible candidate to succeed multilevel-cell (MLC) NAND flash memory. This device has the following characteristics: 3 bit MLC, electroforming-free, self-rectifying, much higher cell resistance than interconnection wire resistance, low voltage operation, low power consumption, long-term reliability, and only an electronic switching mechanism, without an ionic-motion-related mechanism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
98
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 159 publications
(101 citation statements)
references
References 23 publications
2
98
0
Order By: Relevance
“…Programming algorithms like incremental step pulse programming [146][147][148] and closed-loop pulse switching [60,149] have allowed a better control of the multilevel operation in RS devices. The multilevel capability has been reported for a large plethora of RS devices, mainly thanks to the analog dependence of R LRS (R HRS ) on the I SET (I RESET ).…”
Section: Wwwadvelectronicmatdementioning
confidence: 99%
“…Programming algorithms like incremental step pulse programming [146][147][148] and closed-loop pulse switching [60,149] have allowed a better control of the multilevel operation in RS devices. The multilevel capability has been reported for a large plethora of RS devices, mainly thanks to the analog dependence of R LRS (R HRS ) on the I SET (I RESET ).…”
Section: Wwwadvelectronicmatdementioning
confidence: 99%
“…Recently, Hsu et al [ 12 ] and Yoon et al [ 10 ] reported promising rectifying RRAM devices with multilevel resistance states. Recently, Hsu et al [ 12 ] and Yoon et al [ 10 ] reported promising rectifying RRAM devices with multilevel resistance states.…”
Section: Analytical Model For the Writing Margin And Its Confi Rmatiomentioning
confidence: 99%
“…[7][8][9][10][11][12] Although the writing margin issue has been examined in several studies, [13][14][15][16][17] the effect of sneak currents has been overlooked in their analysis, or if any, they mostly relied on the numerical simulation method, which relatively lacked insightful description of the circuits and the mechanisms behind it. [7][8][9][10][11][12] Although the writing margin issue has been examined in several studies, [13][14][15][16][17] the effect of sneak currents has been overlooked in their analysis, or if any, they mostly relied on the numerical simulation method, which relatively lacked insightful description of the circuits and the mechanisms behind it.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, anion migration-related switching mechanism is typically referred to as valence change mechanism (VCM). Till now, electronic memristive devices have been reported in several systems mainly based on two kinds of mechanisms: charge trapping/detrapping [138][139][140][141][142][143][144][145] and metal-insulator transition (MIT). [101][102][103] However, unlike the fruitful findings of the metal cation filaments in the ECM cells, the details of the oxygen migration and the resultant oxygendeficient conductive filaments are still elusive and controversial owing to the difficulty in directly observing the oxygen migration process.…”
Section: Wwwadvelectronicmatdementioning
confidence: 99%